Determining the effect of phase modulation and optimal signal processing on HF communication system reliability and range - Honcharenko, Yurii; Golub, Gennadii; Tsyvenkova, Nataliya; Poleshchuk, Ivan; Denysiuk, Anatolii; Omarov, Ivan; Sukmaniuk, Olena (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers analog high-frequency (HF) communication systems that use broadband signals modulated by the Barker code. The task addressed is to improve the efficiency of analog HF communication systems when transmitting broadband signals. Patterns in the formation of a noise-resistant broadband signal with phase modulation by the Barker code and the operation of the signal spectrum expansion and restoration unit have been investigated. It was established that phase modulation makes it possible to achieve such a spectral width, amplitude of the main peak of the autocorrelation function, and time resolution, which enable effective correlation separation of the usable signal and increases its noise immunity. It has been shown that signal modulation with a five-bit code forms a spectrum with a width of 1 MHz, the amplitude of the main peak of the autocorrelation function is 9 units, and a time resolution of 1–2 μs, which provides an increase in noise immunity to 9 dB at S/N=1 dB compared to the base signal without modulation. The use of a thirteen-bit code allows this indicator to be increased to 13 dB at S/N=–3 dB. The effectiveness of the module for expanding and restoring the spectrum of the modulated signal when transmitting it over a distance without loss of communication quality has been confirmed. Signal modulation with a 5- and 13-bit code, compared to unmodulated, increased the communication range by 9 and 25 times, respectively. The results are attributed to the optimal autocorrelation properties of Barker codes and hardware solutions that form a broadband signal without complicating the circuit. This is explained by the ability of Barker codes to form a narrow correlation pulse and expand the signal spectrum, which reduces sensitivity to narrowband interference. The results are valuable for applications in analog RF communication systems as well as power grids, in particular at low S/N ratios